Exploring Emergency Department (ED) allied health Care Coordination Team (CCT) services provided with frail older adults in the ED at Sir Charles Gairdner Hospital (SCGH) - Murphy, Kim (Curtin University, 2024)
This mixed methods study explored evidence-based allied health care and the services provided by the allied health Care Coordination Team in an Emergency Department (ED) with frail older adults. Allied health are well placed to screen for frailty in the ED, and this screening assists with recognising the frail patient early to improve the quality of care provided by allied health. Access to a multidisciplinary team for frail older adults in the ED is important.